Production Technology for Kopyor Coconut Seednuts and Seedlings in Indonesia - Novarianto, Hengky; Maskromo, Ismail; Sudarsono, S. (International Coconut Community Journal, 2014)
Kopyor coconut is a naturally-occurring mutant having fluffy solid endosperm in stead of the normal one. Similar type of coconut has been found in several other Asian countries, with their distinct local names, such as Macapuno (Philippines), Makhrao Kathi (Thailand), Dikiri Pol (Sri Lanka), Thairu Thengai (India). It is a delicacy coconut to Indonesian and sells as much as ten times higher than normal coconut. In nature, three types of kopyor coconut exist in Indonesia: kopyor tall, kopyor dwarf, and kopyor hybrid. There are three kopyor dwarf varieties (‘Pati Kopyor Green Dwarf’, ‘Kopyor Yellow Dwarf’ and ‘Kopyor Brown Dwarf’) officially released, and one registered tall variety (‘Puan Kalianda Kopyor Tall’). In general, kopyor fruit yield under natural conditions is only < 25% of the total harvested fruits for both the tall and the dwarf types. Traditionally, Indonesian farmers harvest kopyor fruits at ten months after pollination while normal fruits at 11 months. They use the harvested normal fruits for propagation; but cannot guarantee whether or not they would produce korpyor fruit. Adoption of kopyor seedling production through embryo culture has been done. However, the seedling production is slow, while the price is very expensive, thus unaffordable to common farmers. Indonesian Palm Research Institute and Bogor Agricultural University have collaborated to develop alternative approaches to increase kopyor fruit production through the production of seedling that would ensure to produce korpyor fruit through control pollination. Initiated since 2010, the activities successfully overcome uncertainty in kopyor seedling production. Moreover, hybridization among local superior coconut varieties and known kopyor one have been done to broaden genetic background of kopyor trait and to develop breeding population for new kopyor varieties in the future. Overview and update of research progress on korpyor in Indonesia are presented in this paper.